Comparative evaluation of caudal epidural, interlaminar, and transforaminal epidural steroid injection in patients with lumbar spinal canal stenosis - Jyotsna; Amit Kumar; Anshul; Naveen Malhotra; Navya Malhotra; Ritwik Gupta (Asian Journal of Medical Sciences, 2025)
Background: Lumbar spinal stenosis (LSS) is a common degenerative spinal condition which is a major cause of pain and functional disability. Epidural steroid injections with or without local anesthetics have been used for the treatment of spinal pain, particularly for radicular symptoms and spinal stenosis. Aims and Objectives: The primary objective was to compare the efficacy of the three routes in terms of improvement in pain, disability and patient satisfaction. Secondary objectives were to compare the requirement for repeat injections and side effects, if any. Materials and Methods: In this prospective, randomized study, 90 patients with medical evaluation and pain pattern consistent with a diagnosis of LSS were randomized into three groups: Group-I (n=30) patients were administered caudal epidural steroid injection; Group-II (n=30) interlaminar epidural steroid injection; and Group-III (n=30) transforaminal epidural steroid injection (TFESI). The primary objective was to compare the efficacy of the three routes in terms of improvement in pain, disability, and patient satisfaction. Secondary objectives were to compare the requirement for repeat injections and side effects, if any. Results: There was a statistically significant improvement in pain score, Oswestry disability index (ODI) score, and Swiss spinal stenosis questionnaire (SSSQ) score in all groups at all study periods. (P<0.01) The pain scores and SSSQ scores were clinically and statistically significantly lower after TFESI as compared to other groups from 1 month onward after the injection at all study interval periods (P<0.01), whereas ODI scores were better from 3 months onward. Conclusion: All three techniques provide good pain relief and improvement in disability to the patients. TFESI is better than other two techniques in terms of improvement in pain score, treatment outcome, and functional disability.